Dual band low loss metamaterial structure at millimetre wave band - B. A. F. Esmail; H. A. Majid; M. F. Ismail; S. H. Dahlan; Z. Z. Abidin; M. K. A. Rahim (Institute of Advanced Engineering and Science, 2019)
In this paper, the Dual band modified split square resonator (MSSR) metamaterial (MM) structure was designed and numerically investigated at millimetre wave (mm-Wave) frequency range. The proposed structure operated at two resonance frequencies 28 GHz and 32.54 GHz. The dual-band behaviour of the proposed structure because of the self and mutual coupling between two metallic squares of the structure. Furthermore, The MSRR structure performed very well at both resonance frequencies by providing high transmission coefficient, S21, with a loss of -0.3 dB (0.97 linear scale) at lower resonance frequency 28 GHz and -0.18 dB (0.98 linear scale) at upper resonance frequency 32.54 GHz. In this regard, the numerical simulation was conducted to optimize the MSSR structure in such a way that the ratio of effective inductance-to-capacitance (L/C) was raised. As a result, the inherent MM losses were reduced. The robust retrieval algorithm was utilized to reconstruct the refractive index, effective permittivity, and effective permeability and to verify the left-hand property of the proposed structure. The simulation results showed that the MSSR unit cell introduces two regions of the negative refractive index below the lower resonance frequency, 28 GHz and above the upper resonance frequency, 32.54 GHz.